Development and validation of the Essen Intracerebral Haemorrhage Score. Issue 5 (14th December 2005) - Weimar, C; Benemann, J; Diener, H-C
Abstract : Background: Spontaneous intracerebral haemorrhage (ICH) accounts for the highest in-hospital mortality of all stroke types. Nevertheless, outcome is favourable in about 30% of patients. Only one model for the prediction of favourable outcome has been validated so far. Objective: To describe the development and validation of the Essen ICH score. Methods: Inception cohorts were assessed on the National Institutes of Health stroke scale (NIH-SS) on admission and after follow up of 100 days. On the basis of previously validated clinical variables, a simple clinical score was developed to predict mortality and complete recovery (Barthel index after 100 days ⩾95) in 340 patients with acute ICH. Subscores for age (<60 = 0; 60–69 = 1; 70–79 = 2; ⩾80 = 3), NIH-SS level of consciousness (alert = 0; drowsy = 1; stuporose = 2; comatose = 3), and NIH-SS total score (0–5 = 0; 6–10 = 1; 11–15 = 2; 16–20 = 3; >20 or coma = 4) were combined into a prognostic scale with <3 predicting complete recovery and >7 predicting death. The score was subsequently validated in an external cohort of 371 patients. Results: The Essen ICH score showed a high prognostic accuracy for complete recovery and death in both the development and validation cohort. For prediction of complete recovery on the Barthel index after 100 days, the Essen ICH score was superior to the physicians' prognosis and to two previous prognostic scores developed for a slightly modified outcome. Conclusions: The Essen ICH score provides an easy to use scale for outcome prediction following ICH. Its high positive predictive values for adverse outcomes and easy applicability render it useful for individual prognostic indications or the design of clinical studies. In contrast, physicians tended to predict outcome too pessimistically.